Antibiotic Resistance Profile of Selected Uropathogenic Bacteria from Female Patients Attending Hospitals in Parts of Southern Taraba, Nigeria - Brown Samuel Tamuno Cockeye; Agwaranze Dawn Ify; James Samuel Pelentovun; Yusuf Precious Wama (African Journal of Clinical Medicine and Pharmacy Research, 2026)
Urinary tract infections (UTIs) remain a major public health concern among women because of their high prevalence, recurrent occurrence, and rising antimicrobial resistance. This cross-sectional study assessed the prevalence, molecular characteristics, antibiotic susceptibility patterns, and associated risk factors of uropathogenic bacteria among 300 female patients aged 15–55 years in Wukari, Donga, and Ibi Local Government Areas of Southern Taraba. Midstream urine samples were collected and analyzed using standard microbiological procedures. Phenotypic identification was performed for all isolates, while molecular characterization using 16S rRNA gene sequencing was limited to Staphylococcus aureus (1%) and the opportunistic pathogens Brucella intermedia and Alcaligenes faecalis (0.3% each) because of the unusual phenotypic characteristics of the primary isolates. The prevalence of culture-positive UTIs was 13.6%, with Escherichia coli (6.3%) identified as the predominant pathogen, followed by Klebsiella pneumoniae (3%) and Proteus spp. (2.3%). Antibiotic susceptibility testing showed high resistance among Gram-negative isolates to ampicillin, gentamicin, ceftriaxone, and ciprofloxacin, while 12.6% of isolates exhibited multidrug resistance (MDR). Socio-demographic variables, including age, educational level, occupation, and residence, were significantly associated with UTIs (p < 0.05), whereas marital status and religion were not (p > 0.05). Sexual activity emerged as a significant behavioral risk factor, and the type of medication used, improper antibiotic use, and international travel were significantly associated with antibiotic resistance (p < 0.05). Clinically, hematuria and urinary pain or burning sensation were significantly associated with infection (p < 0.05). The study concludes that UTIs and multidrug-resistant uropathogens constitute an important health burden in this population. These findings contribute context-specific evidence on pathogen distribution, resistance patterns, and risk factors, and underscore the need for continuous surveillance, targeted health education, improved hygiene practices, and rational antibiotic stewardship.